KOMPARASI POLA IKAT TARI JEPIN TALI BUI DARI KOTA PONTIANAK DAN KABUPATEN BENGKAYANG - Julia, Julia; Istiandini, Winda; Fretisari, Imma (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research is aimed to determine the similarities and differences in Tali Bui Jepin dance in Pontianak City and Bengkayang Regency. This qualitative comparative descriptive method with ethnocoreology approach was applied as the from of the research. The data in this study was obtained from the results of interviews with informants. Field observations, interviews and documentation were used as the data collecting technique. Extended observation techniques and triangulation techniques were used to test the validity of the data, as well as reduction, presentation and conclusion were used as the analysis technique during in the field observation. comparison of the binding pattern is shown in the binding method, tie pattern, motion, property.The differences are shown in the binding method that starts from the bottom of the foot and starts from the top of the neck, tie pattern, motio and property. The similarities are shown in the weaving pattern in the form of woven baskets, ropes as the property, and dancers as many as 7 people. The results of this study can be used as reference material for teachers or educators and as a reference for cultural arts and skills in learning process in schools, especially in dance subjects.Â Keywords: Comparison, Tie Pattern, Jepin Tali Bui Dance.Â